2016
DOI: 10.1016/j.vaccine.2015.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Protein-prime/modified vaccinia virus Ankara vector-boost vaccination overcomes tolerance in high-antigenemic HBV-transgenic mice

Abstract: Our results indicate that high HBV antigen levels limit the immunological responsiveness to therapeutic vaccination but optimization of the vaccine formulation can overcome tolerance even in the presence of high antigenemia. These findings have important implications for the development of future therapeutic hepatitis B vaccination strategies and potentially also for the stratification of chronic hepatitis B patients for therapeutic vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 39 publications
4
67
0
Order By: Relevance
“…In order to improve immunogenicity and efficacy of therapeutic vaccine candidates for chronic HBV infection, others have used a combination of approaches, such as adjuvants, addition of checkpoint inhibitors, and prime/boost regimens (7,9). Recent studies showed that an optimized, heterologous prime/boost strategy produced strong T and B responses to HBV in various preclinical models of CHB (32)(33)(34). A combination of an HBsAg/HBcAg protein prime with TLR9 agonists followed by a boost with non-replicating modified vaccinia Ankara viruses, optimized for higher level expression of the same antigens was able to overcome the high-level tolerance observed in HBV-transgenic mice (34).…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve immunogenicity and efficacy of therapeutic vaccine candidates for chronic HBV infection, others have used a combination of approaches, such as adjuvants, addition of checkpoint inhibitors, and prime/boost regimens (7,9). Recent studies showed that an optimized, heterologous prime/boost strategy produced strong T and B responses to HBV in various preclinical models of CHB (32)(33)(34). A combination of an HBsAg/HBcAg protein prime with TLR9 agonists followed by a boost with non-replicating modified vaccinia Ankara viruses, optimized for higher level expression of the same antigens was able to overcome the high-level tolerance observed in HBV-transgenic mice (34).…”
Section: Discussionmentioning
confidence: 99%
“…The HepG2.2.15 cell is an HBV-producing human hepatocellular carcinoma cell, which can be used to measure the effects of an immunotherapeutic approach for HBV infection [79]. The inhibition of HBV replication should also be proved in vivo: HBV transgenic mice are an animal model that can be used to assess the effects of HBV therapeutic vaccines [13]. However, the epitopes predicted in the present research are binding to human MHC molecules; thus, the HBV polymerase epitopes targeting MHC molecules of HBV transgenic mice must be predicted and a corresponding vaccine should be constructed.…”
Section: Discussionmentioning
confidence: 99%
“…High HBV antigen levels, especially HBsAg, contribute to specific T cell exhaustion and limit the immunological response to therapeutic vaccination [13]. Persistent exposure of antigens to the immune system is responsible for immune tolerance, which is the reason for the poor clinical responses of therapeutic vaccines constituted by HBsAg and HBcAg.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic vaccination using HBsAg was shown to induce the production of anti‐HBV antibodies in animal models, reducing the antigen levels and thus priming the T‐cell response. However, it was only effective in mice with low viral titres …”
Section: Immune Regulation and Hbsagmentioning
confidence: 99%
“…However, it was only effective in mice with low viral titres. 57 Much has been accomplish in understanding HBV-specific adaptive immunity and its connection with HBsAg. However, innate immune responses in acute or chronic HBV infection remain obscure.…”
Section: Covalently Closed Circular Dna Epigeneticsmentioning
confidence: 99%